Estudo in vitro da inativação fotodinâmica dos microrganismos causadores da esporotricose - Rocha, Amanda Regina (2023)
Sporotrichosis is a zoonosis caused by Sporothrix spp., a fungus that causes a subcutaneous mycosis which can become systemic in immunocompromised individuals. Conventional treatment is based on the prolonged use of antifungals, which can cause many side effects and, to improve on this, it is necessary to study efficient alternatives. The present study aims to show the effectiveness of Antimicrobial Photodynamic Therapy (aPDT) using curcumin as a photosensitizer in the control of S. brasiliensis and S. schenckii, and Candida albicans as a comparative parameter for results. In addition to showing the best parameters for combining aPDT with traditional antifungals against these microorganisms. The fungi were illuminated via a Biotable® (lighting device with 24 evenly distributed LEDs) at a wavelength of 450 nm and a light dose of 31.5 J/cm² with photosensitizer concentrations ranging from 0.75 to 150 μg/mL of curcumin. After determining the Minimum Inhibitory Concentration (MIC) of the itraconazole, ketoconazole and potassium iodide, antifungal therapy was combined with aPDT to verify whether subinhibitory doses of these drugs would be able to eliminate Sporothrix spp. Concentrations of 1.5 to 15 μg/mL of curcumin were used, and the dosages of the drugs reducing the dose from half of the MIC values obtained. An efficient protocol for the inactivation of all microorganisms studied was found with a single application of aPDT and with aPDT combined with conventional treatment. The best results were obtained with aPDT application prior to antifungals, causing the total elimination of the Sporothrix spp. in addition to C. albicans, even with underdoses of both the photosensitizer and antifungal drugs. To better understand the impact of the order of therapies, studies were made of the absorption spectrum of individual compounds and how the combination could influence the dynamics of photobleaching of these compounds. The present study suggests that aPDT using curcumin as a photosensitizer may be a promising alternative to combat sporotrichosis. This treatment would be especially effective in veterinary medicine to be applied in cats as an individual therapy or as a coadjuvant. In the combination of therapies, in vitro protocols result in a synergistic effect in the inactivation of microorganisms. This could improve the treatment of the disease, with a reduction in both the recuperation time and dosage of drugs used, significant benefits of this approach are overall cost reductions and lessened side effects due to preventing the prolonged use of antifungals, while achieving an effective overall treatment.